Guinea-Bissau : The World Bank Group Country Opinion Survey FY 2014 - World Bank Group (World Bank, Washington, DC, 2015)
The Country Opinion Survey in Guinea-Bissau assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Guinea-Bissau perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Guinea-Bissau on 1) their views regarding the general environment in Guinea-Bissau; 2) their overall attitudes toward the WBG in Guinea-Bissau; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Guinea-Bissau; and 4) their perceptions of the WBG’s future role in Guinea-Bissau.